Monoclonal antibodies specific to the E-region of human fibrin(ogen) - Pozniak, T. A.; Kolesnikova, I. N.; Litvinova, L. M.; Kostiuchenko, O. P.; Urvant, L. P.; Khadzhynova, V. E.; Lugovskoi, E. V.; Komisarenko, S. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The monoclonal antibodies (mAbs) of IgG2a type have been obtained. The epitope for them is in the E3 fibrin fragment Aα20–78. The results of turbidity analysis indicate that mAbs and their Fabfragments inhibit the fibrin polymerization. It has been showed by ELISA that these mAbs react with fibrinogen, fibrin, and its E3-fragment, but do not react with (DD)E-complex, in which the interaction of polymerization sites "A"–"a" is realized. We suggest that the "A"–"a" binding screens the epitope zone Aα20–78.